Sineresis, Daya Ikat Air, dan Whey Bebas Yoghurt Susu Kambing dengan Fortifikasi Jahe Merah: Syneresis, Water Holding Capacity, and Whey-Free Goat Milk Yogurt with Fortification of Red Ginger - Yogi Hartono; Triana Setyawardani; Irfan Fadhlurrohman (Universitas Djuanda, 2026)
The study of the effect of fortification with red ginger extract (Zingiber officinale var. rubrum) in the manufacture of goat milk-based yogurt on syneresis, water holding capacity, and free whey aims to determine the effect of adding red ginger extract (Zingiber officinale var. rubrum) with different concentrations on syneresis, water holding capacity, and free whey of goat milk yogurt. The study used a Completely Randomized Design (CRD) with four treatments of red ginger extract concentration (2%, 4%, and 6%) and five replications. The variables measured were syneresis, water-holding capacity, and free whey obtained, which were analyzed using analysis of variance. The results of the analysis of variance (ANOVA) showed that the addition of red ginger extract had no significant effect (P>0.05) on the value of syneresis, water holding capacity, or free whey in goat milk yogurt. The average values obtained were 41.97% for syneresis, 58.19% for water holding capacity, and 65.69% for free whey. The conclusion of the study was that the addition of red ginger extract had no significant effect on syneresis, water binding capacity, and free whey.